HUBUNGAN DUKUNGAN SUAMI DENGAN MOTIVASI IBU BADUTA (18-24 BULAN) DATANG KE POSYANDU KRAJAN BALAI DESA SAPIKEREP: The Relationship between Husband's Support and Two-Year-Old Baby's Mother's Motivation (18-24 months) Came to Posyandu Krajan Sapikerep Village Hall - Ade Lina Dwi Astutik (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Community participation in posyandu is closely related to mother visits. Visits by mothers with toddlers to the posyandu are related to the mother's motivation, for example to get services and monitor the growth and development of their toddlers so that cases of nutritional problems can be resolved early on. Mother's participation in posyandu is influenced by mother's motivation which is influenced by husband's support. The purpose of this study was to analyze the relationship between husband's support and motivation for Mrs. Baduta (18-24 months) to come to Posyandu Krajan Balai Desa Sapikerep in 2023. This study used a correlational analysis design with a cross sectional approach. The sample data are some of the mothers under five at Posyandu Krajan Balai Desa Sapikerep, the inclusion criteria with simple random sampling technique are 51 respondents. Data collection included coding, editing, and tabulating. Then the data were analyzed by computer with the Spearman test p value: 0.05. The results showed that 40 respondents had supportive husbands, 41 respondents had high motivation. Spearman rank test results with p value: 0.000. The conclusion of the study is that there is a relationship between husband's support and the motivation of Baduta's mother (18-24 months) to come to Posyandu Krajan Balai Desa Sapikerep in 2023 (p = 0.000 <0.05). The suggestions put forward are the need for education and outreach to husbands/fathers about the importance of posyandu and appreciation for husbands/fathers taking their children to posyandu regularly.